Secondary prevention in coronary heart disease: baseline survey of provision in general practice - Campbell, Neil C (British Medical Journal, 1998)
Objective: To determine secondary preventive treatment and habits among patients with coronary heart disease in general practice. Design: Process of care data on a random sample of patients were collected from medical records. Health and lifestyle data were collected by postal questionnaire (response rate 71%). Setting: Stratified, random sample of general practices in Grampian. Subjects: 1921 patients aged under 80 years with coronary heart disease identified from pre-existing registers of coronary heart disease and nitrate prescriptions. Main outcome measures: Treatment with aspirin, β blockers, and angiotensin converting enzyme inhibitors. Management of lipid concentrations and hypertension according to local guidelines. Dietary habits (dietary instrument for nutritional evaluation score), physical activity (health practice indices), smoking, and body mass index. Results: 825/1319 (63%) patients took aspirin. Of 414 patients with recent myocardial infarction, 131 (32%) took β blockers, and of 257 with heart failure, 102 (40%) took angiotensin converting enzyme inhibitors. Blood pressure was managed according to current guidelines for 1566 (82%) patients but lipid concentrations for only 133 (17%). 673 of 1327 patients (51%) took little or no exercise, 245 of 1333 (18%) were current smokers, 808 of 1264 (64%) were overweight, and 627 of 1213 (52%) ate more fat than recommended. Conclusion: In terms of secondary prevention, half of patients had at least two aspects of their medical management that were suboptimal and nearly two thirds had at least two aspects of their health behaviour that would benefit from change. There seems to be considerable potential to increase secondary prevention of coronary heart disease in general practice.